Fungsionalisasi Sistem Pembinaan Narapidana dalam Mewujudkan Tujuan Pemidanaan - Rahmat Bayu Wibisono; Rani Yuwafi (Syntax Corporation, 2023)
The model of coaching for prisoners in Correctional Institutions is inseparable from a dynamic, which aims to provide more provisions for prisoners in facing life after completing their sentence (free). The research method used is normative juridical. The results of this study conclude that the functionalization of the prisoner development system in the Penitentiary in realizing the purpose of punishment is as an implementing agency for the guidance of prisoners based on protection through its functions, namely providing education, rehabilitation and also reintegration. The factors that hinder the implementation of the purpose of sentencing in Correctional Institutions are influenced by the factor of integration between the criminal justice sub-systems, the factors of the law that still seem